مدى تأثر المسؤولية الاجتماعية للشركات النفطية بتقلبات أسعار النفط دراسة مقارنة بين كل من شركتي قطر بترول وأرامكو السعودية للفترة (2010-2017) (Revue El-Wahat pour les Recherches et les Etudes, 2020)
This Study Basically Aimed At Clarifying The Significant Importance Of Oil Companies’ Social Responsibility And Identifying The Impact Oil Prices On Companies’ Performance .Also To Present The Different Social Roles Of Oil Companies.Researchers Used Annual And Additional Reports Of Qatar Petroleum And Saudi Aramco Between 2010 And 2017. Researchers Followed The Index Of Social Responsibility Which Consists Of 25 Points.The Study Concluded That The Concept Of Social Responsibility Becomes A Significant Part Of Stakeholder’s Point Of View. Therefore, It Is Unavoidable To Give Social Responsibility Voluntary And Obligatory Importance. Oil Companies Have Big Influence On Society Especially In The Environment Field, Thus, It Puts More Pressure On This Type Of Companies To Assume Their Responsibilities Toward Society To Cover The Negative Aspects Of Their Function. Key Words-  Social Responsibility, Oil Companies, Oil Prices.